Nature of the chemical bonding in D3h [MH3M]+ cations (M = Be, Mg). Issue 11 (8th February 2020) - Penotti, Fabio E.; Cooper, David L.; Karadakov, Peter B.; Ponec, Robert
Abstract: Motivated by the particularly short metal‐metal distance that has been predicted for the D 3 h [BeH3 Be] + cation, comparable to those anticipated for triple bonds, we investigate the nature of the bonding interactions in the D 3 h [MH3 M] + cations (M = Be, Mg). CCSD(T)/cc‐pVQZ calculations are used to determine optimized geometries for all of the various species, including those "capped" by He or Ne atoms (as proxies for an inert gas matrix). The primary tools that are then used to investigate the nature of the chemical bonding are spin‐coupled generalized valence bond calculations and the analysis of localized natural orbitals and of domain‐averaged Fermi holes. The various results for all of the systems considered indicate the presence of highly polar three‐center two‐electron M─H─M bonding character instead of any significant direct metal‐metal bonding. Abstract : The bonding situation in [MH3 M] + cations (M = Be, Mg), which feature very short metal‐metal distances, is shown to be well described by three equivalent highly polar three‐center two‐electron M─H─M bonding units, with the absence of direct metal‐metal bonds.